Effects of postpandemic tourism on the economic income of the hotel sector of the beach playa - Meza Clark, Jorge Edison (2023)
The Playas canton is historically considered one of the sun and beach tourism destinations within the Guayas province, the Ministry of Tourism together with the Decentralized Autonomous Government and the cantonal Emergency Operations Center (COE) at the beginning of the year 2021 partially lifted the sanitary restrictions that governed the Playas spa, it must be established whether the purposes for which the new measures were formulated were fulfilled, in view of this problem we propose as a research objective, to determine the economic impact of post-pandemic tourism on Hotels of the beach resort. In the development of this work, the mixed approach was used, the scope is descriptive and the design was non-experimental, cross-sectional, the data collection technique was the survey, the main results of the research on economic income indicate that it is evident a significant level of affectation according to the data of the Ministry of Tourism and the opinion of the respondents, which fluctuates in 26% of hotels closed at the canton level, the establishments with a highly significant affectation are those of the 3-star category, it is also appreciated that the sector is recovering, although it has not reached the production levels of 2019.